2020
DOI: 10.1007/s00024-019-02408-9
|View full text |Cite
|
Sign up to set email alerts
|

Strong Site Effect Revealed by a New Broadband Seismometer on the Continental Shelf Offshore Nice Airport (Southeastern France)

Abstract: A broadband seismological station (PRIMA) installed offshore Nice airport (southeastern France) reveals a strong amplification effect of seismic waves. PRIMA station was in operation for 2 years (9/2016 to 10/2018) on the outer shelf at a water depth of 18 m. Situated at the mouth of the Var River, this zone is unstable and prone to landslides. A catastrophic landslide and tsunami already occurred in 1979, causing 10 casualties. Given the level of seismicity of the area, it is important to infer the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…uation in the 2-20 Hz band compared with signals recorded outside the bay. This behavior is indicative of sedimentary basins, which are generally characterized by low seismic velocities (e.g., Courboulex et al, 2020;Pratt et al, 2003).…”
Section: Das and Broadband Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…uation in the 2-20 Hz band compared with signals recorded outside the bay. This behavior is indicative of sedimentary basins, which are generally characterized by low seismic velocities (e.g., Courboulex et al, 2020;Pratt et al, 2003).…”
Section: Das and Broadband Comparisonmentioning
confidence: 99%
“…Earthquakes recorded inside Methoni Bay show significant amplification of up to a factor of 10 at frequencies of 1–2 Hz, and stronger attenuation in the 2–20 Hz band compared with signals recorded outside the bay. This behavior is indicative of sedimentary basins, which are generally characterized by low seismic velocities (e.g., Courboulex et al., 2020; Pratt et al., 2003).…”
Section: Das Earthquake Signalsmentioning
confidence: 99%
“…(a) ST5‐PZ2L‐02PZA/P5 and (b) PZC/P18 pore pressure data (depth 3.99 mbsf) compared to temperature measured by sensor PZA/T1 (0.79 mbsf) of ST5‐PZ2L‐02 and (b) SPF‐PZ3L‐01/P18 pore pressure data (depth 25.75 mbsf) compared to seabed temperature at SPF‐PZ3L‐01. Six earthquakes recorded by a broadband seismological station (PRIMA) installed offshore Nice airport (Courboulex et al, 2020) are shown in (b) as vertical lines (from left to right: Norcia‐Central Italy, Digne‐South of France, Chile, Solomon, Limone‐northern Italy, and Monaco‐offshore). Blue line in (b) indicates the local earthquake that occurred in offshore Monaco, 40 km from the study site (Courboulex et al, 2020) is indicated on both figures.…”
Section: Discussionmentioning
confidence: 99%
“…There is indeed a wide recognition that by increasing pore-fluid compressibility free gas reduces excess pore pressure build-up during earthquake loading (DeJong et al, 2014 and reference therein). Hence, despite the strong site effect revealed by Courboulex et al (2020), questions remain as to the possibility that the presence of gas mitigates the earthquake-induced liquefaction potential that Roesner et al (2019) has stressed.…”
Section: Geohazard Implicationsmentioning
confidence: 99%